Revelação do diagnóstico aos filhos infectados por Transmissão vertical do HIV: significados para as mães - Almeida, Pâmela Batista de (2012)
The main aim consisted in comprehend attributed meanings by biological mothers to the process of diagnosis disclosure of HIV/aids to children infected through vertical transmission (VT). It is a qualitative, descriptive-exploratory research. Data production happened from April to June 2012, through semi-structured interviews, respecting ethical aspects of researches with human beings in the Resolution 196/96, following the National Health Board. Subjects were seven biological mothers that assisted their HIV infected children in the Infectious Diseases Services/Pediatric Ambulatory in the University Hospital of Santa Maria. Data were submitted to Thematic Content Analysis, emerging three main categories: I didn t know I had it , The Disease brought good and bad things and Process of diagnosis disclosure to the child. We found that the mother is the main care giver to the infected child, participating on consults, being responsible for the adherence of the child to the treatment and, above all by the diagnosis disclosure. Therefore, the meanings of disclosure are constructed and elaborated since the moment that the mother knows her diagnosis, being characterized as a scary moment, facing questioning of health professionals and through probability of vertical transmission to the child. In addition, the mother also is involved through doubt about fidelity of her partner, holding him responsible by his health condition. But, gradually the mother identifies other factors that favor new meanings to life. Some factors related to quality of life were identified by mothers as positive changes that gave the disease to his life, and others who refer the condition of being sick with aids, how bad situations that have arisen with the disease. Thus, the revelation was characterized as a process in which the information was revealed gradually, as asked by your child or as treatment adherence, presenting or facilitating factors of resistance to the beginning of the process. Finally, as vertical transmission specificity, there were mother s fears of being judged by children for the transmission of the virus.